Introducing advance care planning in patients with advanced COPD. Issue 1 (1st June 2011) - Sives, D; McKeown, A; Raeside, D
Abstract : Background: Advance care planning has become government policy in Scotland and England, and many health professionals are being trained to do it for all patients with advanced life-limiting disease. However there is little evidence of its feasibility and effectiveness. Aim: To design and introduce for all patients with advanced COPD who attend an out-patient clinic an intervention that facilitates ACP, and to evaluate the feasibility and utility of this innovation. Design: piloting of the implementation of structured ACP we introduced an aide memoire (to facilitate ACP) and structured recording sheet into the out-patient clinic for patients with advanced COPD. Findings: We introduced structured ACP into routine out-patient practice and the use of an aide memoire was positively received by health professionals working in the clinic. However ACP conversations were rarely initiated, despite the ACP prompts, unless first raised by the patients themselves. Patients with advanced COPD focused on planning to remain well and rarely had considered end of life planning. In those patients in whom ACP was facilitated hospital admission and interventions such as ventilation were perceived to be to be acceptable particularly when patients had previous experience. Most patients perceived that their eolc would be delivered in hospital. Conclusions: Facilitated ACP proved less useful for initiating conversation for patients with advanced COPD in an out-patient clinic. Patients with advanced COPD rarely consider eolc planning preferring instead to focus on living with and managing their illness and this may prove to be a significant barrier to the facilitation of ACP.